Requirements for Brazilian Outpatient Centers of Excellence in Hidradenitis Suppurativa: Consensus Co-Creative Study - Bellei EA; Shirozaki MEM; Puglia ALP; Esteves de Carvalho AV; Riquena B; Vallilo CC; de Barros D; Tamashiro EY; Cintra G; Duarte GV; da Matta Rivitti-Machado MC; Magalhães RF; et al. (Dove Medical Press, 2023)
Ericles Andrei Bellei,1 Miriam Emi Makinodan Shirozaki,1 Ana Lia Pradella Puglia,2,3 André Vicente Esteves de Carvalho,4 Barbara Riquena,2,5 Camilla Carlini Vallilo,2,3 Danilo de Barros,6 Erika Yumi Tamashiro,2 Gabriela Cintra,2 Gleison Vieira Duarte,7 Maria Cecília da Matta Rivitti-Machado,8 Renata Ferreira Magalhães,9 Ricardo Figueiredo do Nascimento,2 Roberto Tunala,5 Roberto da Silva,10 Wagner Guimarães Galvão Cesar,11 Felipe Garutti Thies2 1Department of Data, Digital, and Innovation, Novartis, São Paulo, Brazil; 2Immunology Franchise, Novartis, São Paulo, Brazil; 3Department of Scientific Operations, Novartis, São Paulo, Brazil; 4Dermatology, Hospital Moinhos de Ventos de Porto Alegre, Porto Alegre, Brazil; 5Department of Medical Affairs, Novartis, São Paulo, Brazil; 6Dermatology Service, Hospital Irmandade Santa Casa de Curitiba, Curitiba, Brazil; 7Dermatology, Instituto Bahiano de Imunoterapia (IBIS), Salvador, Brazil; 8Hospital das Clínicas da Faculdade de Medicina, University of São Paulo (USP), São Paulo, Brazil; 9School of Medical Sciences, State University of Campinas (UNICAMP), Campinas, Brazil; 10Department of Dermatology, Rio de Janeiro State University (UERJ), Rio de Janeiro, Brazil; 11Dermatology, Hospital Alemão Oswaldo Cruz, São Paulo, BrazilCorrespondence: Ericles Andrei Bellei, Novartis Biociências S.A, 90 Av Prof Vicente Rao, São Paulo, 04706-900, Brazil, Tel +55 1155327122, Email eric.bellei@novartis.comBackground: Hidradenitis suppurativa (HS) is a chronic skin condition. Its complexity and impact on patients highlight the need for multidisciplinary care that can address the physical, psychological, and social aspects. Centers of excellence can ideally provide the necessary infrastructure, resources, and expertise to effectively treat HS. However, there are still no consolidated models of centers of excellence in HS, and establishing their foundations is an intricate research challenge. Purposely, design and co-creation as innovation techniques are helpful approaches to this type of research.Methods: In this study, we conducted a co-creation with consensus among HS specialists to propose the criteria and requirements to establish outpatient centers of excellence of HS in Brazil. We followed a linear process with mixed methods in 6 stages.Results: The process resulted in 10 categories for establishing outpatient centers, including their respective requirements, rationale, and classification. The categories include onboarding and welcoming; infrastructure and procedures; infusion therapy; flows and referrals; staffing; disease management; metrics during diagnosis; metrics during treatment; awareness and advocacy; research and education.Discussion: The idealized outpatient centers can play a role in the complete multidisciplinary treatment for HS and advancing the science of healthcare services by providing a focus for research, training, and translation of findings into practice.Keywords: hidradenitis suppurativa, centers of excellence, co-design, consensus, health services research, patient-centered care, community-based participatory research, healthcare innovation